THE EFFECT OF THE PROPORTION OF PINEAPPLE SKIN AND APPLE TEA ON THE CHEMICAL AND ORGANOLEPTIC CHARACTERISTICS OF KOMBUCHA - Sholikha Amalia Putri; Kejora Handarini; Adhania Andika Prayudanti; Andreas Alvin (RADJA PUBLIKA, 2026)
Pineapple peel contains flavonoids and acids, while apple tea is rich in polyphenols and tannins that can increase the functional value of fermented products. The purpose of this study was to determine the effect and determine the best ratio of pineapple peel with apple tea on the chemical and organoleptic properties of kombucha drinks . The study was conducted quantitatively experimentally using a completely randomized design (CRD) with one factor , namely the ratio of pineapple peel and apple tea in making kombucha, with four treatments : P1 (0%:100%), P2 (25%:75%), P3 (50%:50%), and P4 (75%:25%). Fermentation took place for seven days at room temperature (25–30°C). The chemical parameters tested included pH, total titratable acid, total dissolved solids, and total phenolic content, analyzed using Analysis of Variance (ANSIRA) and continued with the Least Significant Difference (LSD) test if there was a significant difference. Organoleptic tests were conducted using the hedonic method for color, aroma, and taste, using the Kruskal–Wallis non-parametric analysis. The results showed that treatment P2 (25% pineapple peel : 75% apple tea) provided the best chemical and organoleptic characteristics. Increasing the proportion of pineapple peel decreased pH and phenolic content and increased total acid and total soluble solids, while the proportion of apple tea produced an optimal balance between chemical and organoleptic properties, including preferred color, aroma, and taste. This indicates that the 25%:75% combination has great potential as an optimal formulation for making kombucha with balanced chemical and organoleptic characteristics.